Island Queens and Mission Wives : How Gender and Empire Remade Hawai'i's Pacific World - Thigpen, Jennifer (Book collections on Project MUSE., 2014)
Island Queens and Mission Wives: How Gender and Empire Remade Hawai'i's Pacific World.